EQUIPMENT TO PREVENT FREEZING OF BACK PRESSURE VALVE OF THE OIL WELL X-MAS TREE - Bashirova, Polina; Muktasipov, Damir; Safiullina, Elena (Journal of Applied Engineering Science, 2022)
This paper presents a device designed to prevent freezing of back pressure valve of the oil well X-mas tree. The work indicated the relevance of the problem, considered the devices used in oil fields and analyzed their shortcomings. The result of the work was an easy-to-use, easy-to-repair and inexpensive device, which is devoid of the shortcomings of the considered models. Analysis and deduction were chosen as the main methods of study. This work contains 8 figures, 2 tables, a bibliographic list of 15 titles.
Keywords: back pressure valve freezing, oil well X-mas tree, oil well operation at low temperatures, flow line heating